Handbook of superconductivity : characterization and applications. edited by David A. Cardwell, David C. Larbalestier, Aleksander Braginski. - Cardwell, David A.; Larbalestier, David C.; Braginski, Aleksander (CRC Press, 2025)
This is the last of three volumes of the extensively revised and updated second edition of the 'Handbook of Superconductivity'. The past twenty years have seen rapid progress in superconducting materials, which exhibit one of the most remarkable physical states of matter ever to be discovered.